Review on models to evaluate coolant activity under fuel defect condition in PWR. (February 2019) - Dong, Bing; Li, Leihao; Li, Chenyue; Zhou, Wentao; Yin, Junlian; Wang, Dezhong
Highlights: Fission product release mechanisms and models from PWR are reviewed. Two procedures of fission product release are presented. Different types of models are described in detail in relation to the two procedures. The CFD method for fission gas release simulation is introduced. Abstract: A review of published work on the fission product release mechanisms and models from pressurized water reactor (PWR) is presented. The influence of fission products on the reactor safety is of great concern, therefore many researchers have utilized different models to evaluate the fission product release amount when fuel rod is defective. Fission product release mainly includes two procedures: from the fuel pellet to the fuel-cladding gap and from the fuel-cladding gap to the coolant. The models describing the two release processes can be categorized into the diffusion model and the kinetic model. The present work aims to provide a comprehensive overview of the fission product release models and the key parameters in these models. This review is necessary and helpful for understanding the release process of fission products, which benefits the fuel failure monitoring and improves the reactor safety.